Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Review - Page 749: 139



Work Step by Step

$\frac{2+3i}{2i}\times\frac{2i}{2i}$ =$\frac{(2+3i)\times 2i}{2i\times 2i}$ =$\frac{4i+6i^{2}}{4i^{2}}$ =$\frac{4i+6(-1)}{4(-1)}$ =$\frac{4i-6}{-4}$ =$\frac{-2(-2i+3)}{-4}$ =$\frac{(3-2i)}{2}$ =$\frac{3}{2}-\frac{2i}{2}$ =$\frac{3}{2}-i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.